Analisis Penciptaan Nilai Bersama Dan Ekuitas Merek Terhadap Kepuasan Pengunjung Hotel - Cut Ani Rohana; Asep Muhamad Ramdan; Acep Samsudin (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The research was aimed at determining how much influence of Value Co-creation has toward ti visitor satisfaction and determining the influence of brand equity on visitor satisfaction at 3-star hotels in Sukabumi City. The research applied descriptive associative research method with quantitative. The populations in the research were visitor of 3-star hotels in Sukabumi City while using simple random sampling method by distributing online questionnaires to 400 respondents. The measurement of the research used semantic differential scale. In the research, the techniques of analzying data applied were validity test, reliability test, normality test, correlation coefficient analysis, determination coefficient analysis, multiple linear regression analysis, simultaneous hypothesis test (F test), and partial hypothesis test (T test) that served to prove the research hypothesis assisted by data processing software, SPSS 24. Keyword: Value Co-creation, Brand Equity, Visitor Satisfaction